YAPIŞIK İKİZLER: OLGU SUNUMU - TOPÇUOĞLU, M. Ata (Cerrahpaşa Medical Journal, 2014)
Background and Design.- As reported in the literature, conjoined or Siamese twins occur once in 50.000- 100.000 of all pregnancies and in 650-900 of all multiple pregnancies. Conjoined or Siamese twins result from incomplete segmentation of a single fertilized ovum between the 8-14th days; if cleavage is further postponed, incomplete twining (2 heads, one body) may occur. They are described by site of union; pygophagus (at the sacrum . most common conjunction); thoracophagus (at the chest); craniophagus (at the head); omphalophagus (at the abdominal wall). Because this situation carries high risk, early diagnosis and management of delivery is extremely important.